Patterns of Care and Outcomes of Carcinosarcoma of the Major Salivary Glands. (29th January 2023) - Talwar, Abhinav; Patel, Evan; Tam, Moses; Zhou, Fang; Hu, Kenneth; Persky, Michael; Vaezi, Alec; Jacobson, Adam; Givi, Babak
Abstract: Objective: Carcinosarcoma of the salivary gland is a rare malignant biphasic tumor. The present study investigates the epidemiology and clinical behavior of carcinosarcoma of the major salivary glands using the National Cancer Database (NCDB). Study Design: Historical cohort study. Setting: NCDB. Methods: All tumors were selected between 2004 and 2018. Patient demographics, tumor characteristics, treatments, and survival were analyzed. Cox regression analysis was performed in surgically treated patients. Results: We identified 154 patients in the NCDB with carcinosarcoma of the salivary gland. Median age at diagnosis was 66 years (interquartile range, 55‐76). Most patients were male (n = 92, 60%). The majority of tumors were in the parotid (n = 122, 79%), followed by submandibular gland (n = 21, 14%). The majority were high grade (n = 93, 95%), and a significant portion had locally advanced disease (pT3‐4; n = 65, 62%). Nodal disease was present in more than one‐third (n = 35, 36%). The most common treatment was surgery with adjuvant radiotherapy (n = 75, 49%). With a median follow‐up of 36 months, the 3‐year overall survival was 57.6% (95% CI, 48.7%‐68.0%). In univariable analysis, advanced pT stage, pN+ disease, and positive margins were associated with worse survival. In multivariable analysis, age (hazard ratio, 1.02; 95% CI, 1.01‐1.04; P = .03) and pT stage (hazard ratio, 2.51; 95% CI, 1.27‐4.95; P = .008) remained significant. Conclusion: Carcinosarcoma is a rare salivary gland tumor that frequently presents at a locally advanced stage. Despite multimodality treatments, the outcomes are poor. In the absence of clinical trial data, these data from the NCDB could guide clinicians in the management of this rare disease.